Faktor-Faktor Yang Mempengaruhi Keputusan Wisatawan Domestik Berbelanja di Pasar Oleh-Oleh Modern (Studi Kasus di Kota Denpasar) - Purnama, Ida Ayu Made Sherly; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 5, Mei 2013 (pp. 226-276), 2013)
Souvenir shop or art market are become a kind of souvenir shopping for a tourist, both for a foreign or domestic, particularly a modern souvenir shop becomes very rapid development. The growth of modern souvenir shop have a bad affected to the traditional souvenir market, apprehensively it would harm the traditional souvenir market. The purposes of this research to determinate the effect of simultaneous or partially between certainty of price, the quality of goods, and facilities towards the decision of shopping the domestic tourist (case study in Denpasar City). The samples in this research were domestic tourist who shopping in modern souvenir shop, taken 120 people with Accidental Sampling Method. The analysis technique used the multiple linear regressions. The results of the analysis was showed, the simultaneously certainty of price, quality of goods, facilities have significantly effect on the decision of domestic tourist to shop at the modern souvenir shop. The coefficient of determination (R 2 ) is 0.681, it means 68.1 percent of decision the domestic tourists to shopping at modern souvenir shop is affected by certainty of price, quality of goods and facilities, while the remaining 31.9 percent are affected by other variable that not include in the research model. Partially, certainty of price, quality of goods and facilities positively and significantly affected to the decision of the domestic tourist to shop in modern souvenir shop. The owner modern souvenir shop in Denpasar City should set a price based on the quality of the goods, maintaining the quality of the offered goods and if it necessary improve the quality of goods, especially in terms of diversity and packaging as well as more attention to the modern souvenir shop physical building.
Keywords: certainty of price; quality of goods; facilities; shopping decision